PROCESSING AND ANALYSIS OF Fligh experiment DATA FOR DETERMINING THE CHARACTERISTICS OF THE MOTION OF A ROUND PARACHUTE on a spiral trajectory AT HIGH ALTITUDES - S. V. Zhurin; S. V. Leonov; Yu. G. Mekhonoshin (Научный вестник МГТУ ГА)
The article is addressed to the analysis of the trajectory parameters and videos obtained during the flight experiment at the launch of meteo-rocket MMP-06 with the purpose to determine major parameters of motion of a round parachute at subsonic speeds in the range of altitudes from 0 to 40 km. The data analysis showed that the trajectory of the parachute represents spiral "stretched" by the wind in the horizontal direction and disturbed by random factors of a non-stationary flow around the parachute. The main parameters of the trajectory are obtained according to the experimental data. Only qualitative analysis of spiral motion paths for round parachutes may be found in the publications on parachute subjects. This article presents the quantitative characteristics of this process.